Electronic Health Record Portals adoption - Tavares, Jorge (2018)
Tavares, J., Goulão, A., & Oliveira, T. (2018). Electronic Health Record Portals adoption: Empirical model based on UTAUT2. Informatics for Health and Social Care, 43(2), 109-125. DOI: 10.1080/17538157.2017.1363759